2021
DOI: 10.48550/arxiv.2111.04392
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does acceleration assist entanglement harvesting?

Zhihong Liu,
Jialin Zhang,
Robert B. Mann
et al.

Abstract: We explore whether acceleration assists entanglement harvesting for a pair of uniformly accelerated detectors in three different acceleration scenarios, i.e., parallel, anti-parallel and mutually perpendicular acceleration, both in the sense of the entanglement harvested and harvesting-achievable separation between the two detectors. Within the framework of entanglement harvesting protocols and the Unruh-DeWitt model of detectors locally interacting with massless scalar fields via a Gaussian switching function… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…An interesting work that studies how the acceleration can assist entanglement harvesting is presented in Ref. [80]. The authors investigate three different acceleration scenarios using the Unruh-DeWitt particledetector model -this is the main difference between the procedure that we have used here.…”
Section: Entanglement Harvestingmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting work that studies how the acceleration can assist entanglement harvesting is presented in Ref. [80]. The authors investigate three different acceleration scenarios using the Unruh-DeWitt particledetector model -this is the main difference between the procedure that we have used here.…”
Section: Entanglement Harvestingmentioning
confidence: 99%
“…Relativistic quantum entanglement has been investigated in different setups. Many of these works reveal how entanglement is an observer-dependent quantity, in addition to unraveling how the effects of entanglement dynamics can depend on the space-time separation between atoms, as well as the space-time dimension [70][71][72][73][74][75][76][77][78][79][80][81][82]. Here we wish to report progress on the discussion of entanglement dynamics for two-level systems in non inertial reference frames.…”
Section: Introductionmentioning
confidence: 99%
“…The entanglement harvesting phenomenon has attracted a lot of attention and been examined in a wide variety of circumstances, e.g., with detectors in accelerated motion, in the presence of completely reflecting boundaries and in spacetimes with nontrivial topology. It was demonstrated that the acceleration of detectors, which leads to the well-known Unruh effect, can surprisingly assist entanglement harvesting in certain cases [12,14] and the reflecting boundary plays a double edged role in entanglement harvesting, i.e., degrading in general the harvested entanglement while enlarging the entanglement harvesting-achievable parameter space [15]. More intriguingly, one also finds that entanglement harvesting is quite sensitive to the intrinsic properties of spacetime including its dimension [13], topology [16], curvature [17][18][19][20][21][22], and causal structure [23][24][25], and thus the phenomenon of entanglement harvesting may provide a tangible way to probe the properties of spacetime [16,18,21,22] and even distinguish a thermal bath from an expanding universe at the same temperature [17].…”
Section: Introductionmentioning
confidence: 99%
“…The extracted entanglement can be further distilled into Bell pairs [26], indicating that in principle the vacuum is a resource for quantum information tasks. A considerable amount of research on this phenomenon has since been carried out [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], and the process has come to be known as entanglement harvesting [43,45]. In general it depends on the properties and states of motion of the detectors, and has been investigated for both spacelike and non-spacelike detector separations [46][47][48].…”
Section: Introductionmentioning
confidence: 99%

Entanglement harvesting of three Unruh-DeWitt detectors

Mendez-Avalos,
Henderson,
Gallock-Yoshimura
et al. 2022
Preprint
Self Cite